The effect of self-concept and learning independence on achievement motivation of the students at X University in Samarinda - Nabilla, Tri Izatin; Nur Rahma, Dian Dwi (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2024)
This study aims to investigate the influence of self-concept and independent learning on achievement motivation. This research used quantitative approach and simple random sampling technique. The sample was 117 students from the Faculty of Tarbiya and Teacher Training at X University. Data were collected using scales measuring achievement motivation, self-concept, and independent learning. Multiple linear regression technique was used to analyze the data. The results revealed that self-concept and independent learning significantly influence students' achievement motivation, with self-concept having a significant positive impact on achievement motivation. Future researchers are encouraged to explore other factors that may exert an influence on students' learning motivation. Furthermore, it is recommended for future studies to expand the sample size to provide better representation of a broader population.